Orange-derived and dexamethasone-encapsulated extracellular vesicles reduced proteinuria and alleviated pathological lesions in IgA nephropathy by targeting intestinal lymphocytes - Zhang, Wang; Yuan, Ye; Li, Xiang; Luo, Jiao; Zhou, Zhanmei; Yu, Lei; Wang, Guobao (Frontiers in Immunology, 2022)
Current evidence highlights the critical role of the gut-kidney axis in the pathogenesis of IgA nephropathy (IgAN). However, few attempts have been made to explore targeted intestinal immunity therapy. This research aims to develop an oral intestine targeting medication based on extracellular vesicles (EVs) and investigate its therapeutic efficacy in IgAN.EVs were isolated from orange juice and electroporated with dexamethasone sodium phosphate (DexP). After oral administration, EVs-DexP was picked up by lymphocytes in the submucosal area of ileocecum. EVs-DexP outperformed DexP not only in suppressing lymphocyte stimulation in vitro but also in alleviating renal pathological lesions in the IgAN mouse model. Clinical improvement was accompanied by a reducing IgA secreted by the intestine and a decreasing IgA + B220 + lymphocytes in Peyer's patches. The present study develops a cost-effective, biofriendly EVs-based glucocorticoid strategy for IgAN.